Kolaviron and L-Ascorbic Acid Attenuate Chlorambucil-Induced Testicular Oxidative Stress in Rats - Ebenezer Tunde Olayinka; Ayokanmi Ore (Journal of Toxicology)
Chlorambucil (4-[4-[bis(2-chloroethyl)amino]phenyl]butanoic acid) is an alkylating agent, indicated in chronic lymphocytic leukaemia. Kolaviron (KV), a biflavonoid complex from Garcinia kola, and L-ascorbic acid (AA) are known to protect against oxidative damage in vivo. This study evaluates the protective capacity of KV and AA on chlorambucil-induced oxidative stress in the testes of rat. Twenty male Wistar rats (180–200 g) were randomized into four groups: I: control, II: chlorambucil (0.2 mg/kg b.w.), III: 0.2 mg/kg chlorambucil and 100 mg/kg KV, and IV: 0.2 mg/kg chlorambucil and 100 mg/kg AA. After 14 days of treatments, results indicated that chlorambucil caused significant reduction (P<0.05) in testicular vitamin C and glutathione by 32% and 39%, respectively, relative to control. Similarly, activities of testicular GST, SOD, and CAT reduced significantly by 48%, 47%, and 49%, respectively, in chlorambucil-treated rats relative to control. Testicular MDA and activities of ALP, LDH, and ACP were increased significantly by 53%, 51%, 64%, and 70%, respectively, in the chlorambucil-treated rat. However, cotreatment with KV and AA offered protection and restored the levels of vitamin C, GSH, and MDA as well as SOD, CAT, GST, ACP, ALP, and LDH activities. Overall, kolaviron and L-ascorbic acid protected against chlorambucil-induced damage in the testes of the rat.